2021
DOI: 10.1784/insi.2021.63.5.280
|View full text |Cite
|
Sign up to set email alerts
|

Towards airborne laser Doppler vibrometry for structural health monitoring of large and curved structures

Abstract: Laser Doppler vibrometry is an important sensing technology for many structural health monitoring (SHM) methods, such as modal analysis. However, when it comes to large civil structures, for example historic structures and bridges, the applicability of laser Doppler vibrometry is significantly constrained by inaccessible remote surfaces. Some of these surfaces are fully inaccessible to a ground-mounted laser Doppler vibrometer (LDV), while others are partially inaccessible, and measurements are only possible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…An LDV employs the optical coherent detection method and is widely used in industry, vehicles, robots, aerospace, biomedical field, etc. [2][3][4][5][6][7][8][9]. Compared with the contact sensors, the LDV attracts widespread attention because it enables non-contact measurements.…”
Section: Introductionmentioning
confidence: 99%
“…An LDV employs the optical coherent detection method and is widely used in industry, vehicles, robots, aerospace, biomedical field, etc. [2][3][4][5][6][7][8][9]. Compared with the contact sensors, the LDV attracts widespread attention because it enables non-contact measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Other scholars claimed that they have built a UAV-LDV system to achieve aerial testing. However, the utilization of the UAVs in these systems is limited to the placement of reflective targets [44], for the enhancement of the reflected laser intensity or the carriage of acoustic exciters [45], for the replacement of manual tapping, or carrying mirrors to reflect the laser light from stationary LDVs [46,47]. Their actual tests still rely on stationary LDVs, and the purported UAV-LDV systems have not been fully realized.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, they provide valuable insights into potential strategies for mitigating turbulencerelated challenges, particularly in LDV applications deployed on drones. 9,10 Gibson et al observed fluctuations in the optical path length (OPL) with root mean square (RMS) values of around ∼ 0.2 µm over 1-meter optical path when wind speeds ranged from 1 m/s to 5 m/s. 11 Turbulence occurs within the optical path, and longer optical paths lead to more pronounced turbulence effects.…”
Section: Introductionmentioning
confidence: 99%